Post Operative Pulmonary Complications Following Surgery for Congenital Heart Disease (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Objective: To identify the incidence and related factors for pulmonary complications and its impact on outcome in patients subjected to surgery for congenital heart disease (CHD).Methods: The sample comprised 141 patients of both genders, subjected to surgery for CHD, during 3 months period from 1st July 2014 to 30th September 2014. The data were obtained from newly improvised Congenital Heart Surgery Database.Results: Twenty eight (20%) patients developed some form of pulmonary complications. Age, weight, length and body surface area are significantly low among them (p